Karakteristik Morfometrik dan Meristik Ikan Putak Notopterus Notopterus Melalui Tengkulak di Tiga Kabupaten di Sumatera - Mulyani, Rahma; Yusanti, Indah Anggraini; Seno, Mahmud Bimo; Humairani , Humairani (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The knife fish Notopterus notopterus a relative of the Belida fish that can be found in river or swamp waters on the islands of Sumatra, Java, and Kalimantan. Differences in environmental conditions where the knife fishlive such as current, dissolved oxygen, temperature, salinity, and food availability can affect the distribution and morphological variations of the fish. Variations in fish morphology can be measured by observing fish morphometrics. The purpose of this study was to determine the morphometric characteristics, meristics and ratio of the Knife fishin South Sumatra. The method used in this study was a descriptive survey method using the Knife fishas the object of research. Sampling of the knife fishwas carried out using the purposive sampling method at 3 sampling stations, namely station 1, the knife fishshelter in Epil Village, Musi Banyuasin Regency, Station 2 located at BBI Sukarela, Banyuasin Regency, and Station 3, the knife fish broker located in Sianjur 3, Palembang City. The samples obtained were observed using previous research references and processed with simple analysis of the results of the study showed that from the three stations, there were 11 similar characters that showed positive allometric status, namely head width (HW), distance between anal and pelvic fins (PEFL), dorsal fin length (DFL), upper anal fin width (NAFL), dorsal fin width (NPF), head depth (HD), anal fin width (AFW), body height (BD), distance from lateral line to lower body (DLB), distance from upper lateral line (DLU), and dorsal fin bone width (DSW). Positive allometric status means that the increase in total length (TL) is slower than the increase in other morphometric characters. In addition, the 3 stations have 3 characters with strong relationship status, namely standard length (SL), dorsal fin length (DFL), and dorsal fin width (NPF). Strong correlation means that the greater the total length (TL), the greater the morphometric character comparison. Based on the data at stations 1 and 3, the sex ratio is dominated by male putak fish, so it can be said that the knife fish population at stations 1 and 3 is not ideal.